The Implementation of Cambridge Curriculum in the International Elementary School - Mustadi, Ali; Junaidi, Adzra Diza (International Journal of Elementary Education, 2024)
Development of the era affects education to keep on growing and its triggers schools for persist in being innovative, and one of the alternatives was using international curriculum, among others is Cambridge Curriculum. This research aims to analyze the implementation of the Cambridge Curriculum at International Elementary School from the school and class level in terms of the planning, implementation, and evaluation. It used the case study approach with the type of descriptive research design with the subject consisting of teachers, principals, curriculum teams, students, and Cambridge Curriculum subject classes. The data collection was conducted through interviews, observations, and documentation. The data validation was through triangulation and increased persistence using the interactive model data analysis technique. The results of this research indicate (1) there is an inter-teacher discussion forum entitled Curriculum Day, used in planning both levels of curriculum implementation and school-level evaluation, (2) implementation of the Cambridge Curriculum in the grade level is filled with hands on activities and uses sources and digital media such as Twinkl and Grammarly, and (3) besides the written test, there are non-written tests for learning evaluation such as I-STEAM EXPO and SLC, and the way of how Cambridge Curriculum’s implemented showed relevance between the development of education with their needs. This research concluded the implementation of Cambridge Curriculum in the school executed well for all stages in both levels and give advantages to the school’s development.